Isoliquiritigenin Confers Neuroprotection and Alleviates Amyloid-β42-Induced Neuroinflammation in Microglia by Regulating the Nrf2/NF-κB Signaling - Fu, Yue; Jia, Jianping (Frontiers in Neuroscience, 2021)
Background: Neuroinflammation and oxidative stress are two major pathological characteristics of Alzheimer’s disease (AD). Isoliquiritigenin (ISL), a natural flavonoid isolated from the root of liquorice, has been shown to exert inhibitory effects on inflammatory response and oxidative stress. Objectives: The main purpose of this study is to assess the influence of ISL on inflammatory response and oxidative stress in BV2 cells stimulated with amyloid-β oligomers (AβO), and to explore the underlying molecular mechanisms. Methods: MTT and lactate dehydrogenase (LDH) cytotoxicity assays were used to assess the toxic or protective effects of ISL. The expression levels of interleukin-1β, interleukin-6, and tumour necrosis factor-α were assessed by quantitative real-time polymerase chain reaction (qRT-PCR) and enzyme-linked immunosorbent assays (ELISA). Morphological changes in BV2 cells were assessed by immunofluorescence method. Nitric oxide (NO) assay kit was used to determinate the NO production. Western blot, qRT-PCR and immunofluorescence were used to explore the underlying molecular mechanisms. Results: ISL treatment reduced the production of inflammatory cytokines and NO, and alleviated the morphological changes in BV2 cells induced by AβO. ISL treatment further protected N2a cells from the toxic medium of AβO-stimulated BV2 cells. ISL activated nuclear factor erythroid-2 related factor 2 (Nrf2) signaling and suppressed nuclear factor-κB (NF-κB) signaling in BV2 cells. Conclusion: ISL suppresses AβO-induced inflammation and oxidative stress in BV2 cells via the regulation of Nrf2/NF-κB signaling. Therefore, ISL indirectly protects neurons from the damage of toxic conditioned media.